TCF21 variant is a risk factor for coronary artery disease and will it be a prognostic marker?. (25th November 2020) - Temtem, M; Serrao, M; Pereira, A; Santos, M; Mendonca, F; Sousa, J.A; Monteiro, J; Sousa, A.C; Freitas, S; Henriques, E; Guerra, G; Ornelas, I; et al.
Abstract: Background: TCF21 gene, encodes a basic-helix- loop- helix transcription factor, playing a critical action in the development of epicardial progenitor cells that give rise to coronary artery smooth muscle cells (SMC) and cardiac fibroblasts. Recent data suggest that TCF21 may play a role in the state of differentiation of SMC precursor cells that migrate to vascular lesions and contribute to fibrous cap. Purpose: Investigate the association of TCF21 rs12190287G>C variant with coronary artery disease (CAD) in a Portuguese population and its role on the prognosis. Methods: Case-control study with 3120 participants, 1687 coronary patients with at least 75% obstruction of a major coronary artery and 1433 controls. Genotyping used the TaqMan technique (Applied Biosystems) and then a univariate and multivariate logistic regression analysis were performed. After a mean follow-up of 5.01±4.2 years (interquartile range 1.96–7.57), the occurrence of the combined Major Adverse Cardiovascular Events (MACE) (Cardiovascular Mortality, non-fatal Myocardial Infarction, new Revascularization, Cerebrovascular Disease and Peripheric Vascular Disease) were registered and analysed by Cox regression. Finally, Kaplan-Meier survival estimate was performed. Results: In the total population, GC+CC genotype was found to be associated with CAD with an OR of 1.285; CI: 1.022–1.614; p=0.031. After multivariate logistic regression, adjusted to traditional risk factors, the association with CAD remained significant for this genotype (OR=1.340; CI: 1.042–1.723; p=0.022).After Cox regression adjusted for confounding variables (age and sex, hypertension, diabetes, smoking, dyslipidemia, eGFR, Ejection fraction <55) the mutated genotype remained a significant predictor of MACE (HR=1.420; CI: 1.032–1.953; p=0.031). The individuals carrying the mutated allele (GC+CC) at the mean follow-up showed an event probability of 36.1%, whereas the wild population (GG) presented only 23.4%. The Log-Rank test showed significant differences between the two curves (p=0.019). Conclusion: The mutated TCF21 variant can provide a new marker to identify patients at high cardiovascular risk and may representa potential target for gene therapy in future. Funding Acknowledgement: Type of funding source: None